(untitled) - Dobbs, Jeannine (Cambridge, UK, 2001)
This book provides tips and suggestions to help language teachers use their classroom boards more effectively and efficiently. It provides more than 130 activities for the board to help teachers both teach and assess their ESL, EFL, or foreign language students. These activities will also provide opportunities for students, whatever their age or level of competency, to: - learn and practice specific lexical, phonetic, or grammatical items - attain increased fluency in their writing, reading, listening, and speaking skills - teach and learn from their peers - benefit from visual and kinesthetic learning strategies - practice self-assessment - get to know each other and other cultures better - have fun during the learning process.
Keywords: Language and languages,Teaching; Study and teaching,Aids and devices